ANALISIS DAMPAK PEMBANGUNAN TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Libraningrum, Dionisia; Santoso, Dwi Budi (Journal of Development Economic and Social Studies, 2023)
Economic growth is an indicator of a country’s economic activity. It can also be used to analyze the country’s economic development. However, in reality, Indonesia’s economic growth is still slower than its four ASEAN peer countries, i.e. Malaysia, Vietnam, Thailand, and the Philippines. In terms of internet usage, those countries also have a far higher percentage of internet users. Using the simultaneous model with Two-Stage Least Squares (2SLS), this research attempts to estimate the impact of information and communication technology development on Indonesia’s economic growth and to analyze factors affecting the development of information and communication technology in the country. This research uses the 2012, 2015, and 2019 data of Statistics Indonesia, as well as the 2012-2020 interval data of the same source. This study finds that the development of information and communication technology significantly affects Indonesia’s economic growth and that factors affecting the development of information and communication technology in Indonesia are education index and export. Based on the findings above, the government and related parties are suggested to boost educational equity and intensify international trade that can enhance the use of technology in Indonesia.